EFEKTIFITAS JUS BUAH BIT TERHADAP PENINGKATAN KADAR HAEMOGLOBIN IBU HAMIL DENGAN ANEMIA - Dian Zuiatna; Nurrahmaton Nurrahmaton; Ziadatun Amini Harahap (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2023)
Anemia in pregnant women according to the highest age, namely 15-24 years as much as 84.6%, aged 24-34 years as much as 33.7%. Anemia occurs due to physiological changes and is exacerbated by malnutrition. Handling anemia can use 2 ways, namely pharmacological and non-pharmacological. One example of non-pharmacological treatment is using beets (Beta Vulgaris). The content of beets is Vitamin C, iron, zinc. The purpose of this study was to determine the effect of beetroot juice (beta vulgaris) on increasing hemoglobin levels in pregnant women with anemia in Sipaku Village, Area Simpang Empat District, Asahan Regency. The research design uses a Pre-Experimental Design approach in the form of One Group Pre-test and Post-test with a Paired t-test. The research population was 11 people. The sampling technique is non-probability sampling with purposive sampling technique. The results of the t test with a confidence level of 95% show that the P-value = 0.000 <0.05. The conclusion from this study is that there is an effect of giving beetroot juice on increasing hemoglobin levels in pregnant women with anemia in Sipaku Area Village, Simpang Empat District, Asahan Regency. It is hoped that the results of this study can be an option for pregnant women to treat anemia in a non-pharmacological way, namely using beetroot juice